(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2023)
The effect of thermosonication at three temperatures on the growth of spoilage bacteria in Costeño cheese was investigated. Bacterial counts were fitted to primary models such as Gompertz, Huang, and Buchanan. Polynomial equations were used to describe the effect of thermosonication on the specific growth rate. The mean square error (MSE), bias factor (Bf), and accuracy factor (Af) were used to evaluate the performance of predictive models. The most severe treatment applied in this study was thermosonicated at 40 kHz at 60°C, which led to an increased latency phase and a decreased specific growth rate of the spoilage bacteria analyzed. The specific growth rate values obtained from the Gompertz and Buchanan models were employed to construct polynomial equations. These secondary models had bias factors and accuracy factors close to one, indicating that the polynomial models were able to describe microbial growth in cheese. These results could likely contribute to initiating the application of thermosonication to extend the shelf-life of Costeño cheese